JUDGE'S EX OFFICIO RIGHTS TO A FAIR VERSTEK DIVORCE DECISION AT THE PALOPO RELIGIOUS COURT - Pasinian, Suleha Nurazisah; Yusmad, Muammar Arafat; Abdain; Assaad, A. Sukmawati; Takdir (Universitas Islam Negeri Alauddin Makassar, 2023)
Judges have the authority to hear and decide divorce cases, which are delegated to them in Court autonomously and without influence from outside parties in accordance with applicable regulations. This research aimed to reveal the use of the Judge's ex officio rights regarding fair divorce decisions at the Palopo Religious Court. This research was empirical, using a normative and juridical approach. The data collection techniques used interviews, observation, and documentation. The data analysis technique was carried out in three steps, namely reduction, presentation, and drawing conclusions. The research results showed that the use of ex officio rights by the Judge of Palopo Religious Court regarding the verstek decision in a fair talaq divorce case was the determination of a decision outside the appellant’s petitum by the Judge by determining the level of living for the ex-wife due to the woman's lack of awareness to demand her rights after the divorce as evidenced by her absence at the trial, which is based on limitations. The execution of the Palopo Religious Court regarding the provision of mut'ah and iddah living in Decision number 25/Pdt.G/2023/PA.Plp was on consignment. The perspective of Islamic law regarding women's rights after divorce in decision number 25/Pdt.G/2023/PA.Plp and decision number 7/Pdt.G/2023/PA.Plp at the Palopo Religious Court was the provision of iddah, mut’ah, madhiyah, hadhanah and dowry owed to the ex-wife, according to the limitations.